Development an Android-Based Game “Chemical Hydro Adventure” for Learning Hydrocarbon Material - Nadifa Nur Permata; Achmad Lutfi (JURNAL PENDIDIKAN SAINS UNIVERSITAS MUHAMMADIYAH SEMARANG, 2022)
This research aimed to develop an Android-based Game named Chemical Hydro Adventure as media learning of hydrocarbon materials to improve learning outcomes and quality. This research used Research and Development (R&D) methods within three aspects assessed: validation by the experts, the practicality of the game based on students’ questionnaire results distribution, and the game’s effectiveness based on improving learning outcomes. The results showed 86.13% highly relevant, meaning that the game media was suitable to validity criteria, thus, it could be tried and tested. The practical results obtained 94% very practical, meaning the game could facilitate the students to learn hydrocarbon materials. In addition, there were significant effects of the game reaching minimum completeness, meaning the game was a very effective tool. Therefore, the game developed was reasonable to be use and it was expected chemistry teachers could apply and use it properly. Furthermore, it could facilitate the chemistry teaching and learning process of hydrocarbon materials.